TUJUAN PENDIDIKAN ISLAM PERSPEKTIF INSAN KAMIL: PURPOSE OF ISLAMIC EDUCATION PERSPECTIVE HUMAN KAMIL - zainuddin karim zainuddin (IAI DDI Mangkoso, 2022)
The aim of this article is to discuss how the meaning of man is perfect in view of the purpose of Islamic education. This research is a type of literature research. Library research is a method used by reviewing books related to the theme discussed. In collecting data, the author uses a literature study, which is research conducted by using data related to the purpose of Islamic education from books, journals, newspapers, the internet and other relevant sources. The results of this study suggest the purpose of Islamic education oriented towards human beings. That is, it explains man's position as a servant of God, the purpose of man's creation, and how man obtains prosperity and happiness in this world and in the Hereafter. Humans cannot become human beings without going through the process of education, through education humans can be educated both intellectually intelligent, spiritually intelligent, and intelligently behaved.